PENERAPAN METODE EXPERIENTIAL LEARNING TERHADAP PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP - Maman Lesmana; Evan Farhan Wahyu Puadi; Abdul Rosyid (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2016)
the application of the method of Experiential Learning to increased Ability of JUNIOR HIGH SCHOOL students ' Mathematical Connections. This research aims to study the mathematical connection capacity of students who get the experiential learning with learning methods that get the conventional learning. This research is a research quasi experimental design. The results of the initial test data analysis retrieved tarithmetic t = -1.49 and ttabbel = 2.0252. because -2.0252 < -1.49 < 2,0252 or -ttabble < tarithmetic < ttabble, so the ability of mathematical connections both classes before the second treatment given in the same class are the same. While the analysis of tests late retrieved Uarithmetic = 226.5 and Utabbel are U(20)(20) = 138, because 226.5 > 138 or Uarithmetic > Utabble percentage, and average student response towards the learning of 33.2% this means that almost half of the students give experential learning method in response to learning in mathematics. A comparative analysis of the average score gains with N-Test-U earned Uarithmetic = 410 and U of the table is U(20)(20) = 138. Because Uarithmetic > Utabble or 410 > 138, then there is an increased ability of mathematical connection that uses the experiential learning learning better from the ability of mathematical connections that use conventional learning